2021
DOI: 10.1177/17475198211051910
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis and biological evaluation of (2E,4E)-4-arylidene-2-styryl-5-oxopyrrolidine derivatives

Abstract: Many marine alkaloids possess interesting structures and antitumor activities. Thus, we have synthesized (2 E,4 E)-4-arylidene-2-styryl-5-oxopyrrolidine derivatives of the marine alkaloids, rhopaladins A–D. The cytotoxicities of these derivatives against C-33A, CaSki, SiHa, HeLa, HepG2, and LO2 cells are evaluated by MTT assays. The results show that (2 E,4 E)-2-(4-chlorostyryl)-4-benzylidene- N-cyclohexyl-1-(4-fluorophenyl)-5-oxopyrrolidine-2-carboxamide significantly inhibits cancer cell proliferation, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Marine alkaloids are widely found in marine organisms and have diverse physiological activities, such as the antifungal activity, antimicrobial activity, anti-inflammatory activity, and cytotoxicity ( Martin and Jiang, 2010 ; Dyshlovoy et al, 2016 ; Tanaka et al, 2016 ; and Kong et al, 2021 ). Studies have shown that the marine alkaloids rhopaladins A–D can inhibit the activity of cyclin-dependent kinase 4 and C-erbβ-2 kinase and promote the apoptosis of tumor cells ( Janosik et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marine alkaloids are widely found in marine organisms and have diverse physiological activities, such as the antifungal activity, antimicrobial activity, anti-inflammatory activity, and cytotoxicity ( Martin and Jiang, 2010 ; Dyshlovoy et al, 2016 ; Tanaka et al, 2016 ; and Kong et al, 2021 ). Studies have shown that the marine alkaloids rhopaladins A–D can inhibit the activity of cyclin-dependent kinase 4 and C-erbβ-2 kinase and promote the apoptosis of tumor cells ( Janosik et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2 E , 4 E )-2-(4-chlorostyryl)-4-benzylidene-N-cyclohexyl-1-(4-fluorophenyl)-5-oxopyrrolidine-2-carboxamide (RPDPRO) ( Kong et al, 2021 ).…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Hence, Rhopaladins’ analogs ( E )-2-aroyl-4-arylidene-5-oxopyrrolidine (RPDP serial chemicals) have been synthesized by one-pot method using Ugi condensation and intramolecular S N Cyclization ( Zeng et al, 2013 ; Wang et al, 2020b ), and ( E )- N -( tert -butyl)-2-(4-chlorobenzoyl)-4-(4-fluorobenzylidene)-1-isopropyl-5-oxopyrrolidine-2-carboxamide (RPDPB for short) effects on proliferation, apoptosis and E6/E7 mRNA of cervical cancer CaSki cells were studied ( Zhu et al, 2020 ). Further, in order to obtain compounds with better apoptosis inducing activity of tumor cells, analogs of Rhopaladins (2 E ,4 E )-4-arylidene-2-styryl-5-oxopyrrolidine (RPDPR serial chemicals) were synthesized after structural optimization ( Kong et al, 2021 ). Among them (2 E ,4 E )-4-chlorobenzylidene-2-(4-chlorostyryl)- N -cyclohexyl-1-(4-fluorophenyl)-5-oxopyrrolidine-2-carboxamide (RPDPRH for short, see Scheme 1 ) has better anti-hepatoma activity and low hepatotoxicity ( Zeng et al, 2020 ; Zhu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%